Exploring of the Pharmacy Industry of Kazakhstan: Theory, Implementations and Model of Waste Management - ORYNBETk, Perizat Zh.; MUSSABALINA, Dinara S.; NURLANOVA, Nailya K.; KIREYEVA, Anel A.; SATPAYEVA, Zaira T. (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023, 2023)
The purpose of this research is to study the level of development of the pharmaceutical industry, to develop recommendations to household disposal of pharmaceuticals and to propose a waste management model to climate change. The goal was achieved solution of the following objectives: analysis of the pharmaceutical industry in Kazakhstan, including within the framework of the EAEU; study of the problem of waste management and approaches to its solution; development of proposals for the management of medical waste processing. In our study we are using the following methodological algorithm of scientific research provision: analytical review of the current situation, conducting a sociological survey, building a management model in the form of a “flowchart” based on the use of a systematic approach. In the result of the provided research, it was proved that the volume of pharmaceutical drugs production is constantly growing and almost does not decrease. At the same time, the development of the pharmaceutical industry has increased the growth of waste. Therewith, the strategy of management must be focused on prevention and reduction of such effect, at finding opportunities for managing, but at the same time so as not have a negative influence on the environment. Because the environment is one of the most important aspects of human life.